CTNI-24. A PHASE 2 STUDY OF TRAMETINIB FOR PATIENTS WITH PEDIATRIC GLIOMA WITH ACTIVATION OF THE MAPK/ERK PATHWAY. TRAM-01. (9th November 2020) - Perreault, Sébastien; larouche, Valérie; Tabori, Uri; Hawkins, Cynthia; Lippe, Sarah; Ellezam, Benjamin; Décarie, Jean-Claude; Théoret, Yves; Metras, Marie-Élaine; Sultan, Serge; Cantin, Édith; Routhier, Marie-Ève; et al.
Abstract: BACKGROUND: Pediatric low-grade gliomas (PLGG) are the most frequent brain tumors in children. It is known that the majority of PLGG have activation of the MAPK/ERK pathway. METHODS: This multicenter phase II included three progressing/refractory PLGG groups: NF1 patients, KIAA1549-BRAF fusion patients and patients with other activation of the MAPK/ERK pathway (excluding V600E). Primary objective is to evaluate overall response rate after daily oral trametinib administration for 18 cycles each 28 days duration. Secondary objectives include the assessment of progression-free survival, tolerability of trametinib, serum levels of trametinib and evaluation of quality of life during treatment. RESULTS: As of June 1 2020, 37 patients have been enrolled (NF1: 7 patients, KIAA1549-BRAF fusion: 22, other: 8 (including 5 patients with FGFR1 alterations). Median age is 9.3 years (range 2.3–25.4). Median follow-up is 8.8 months (range 0–19.3). Twenty-eight patients are evaluable. Best response includes: 4 partial response (PR) (14%), 5 minor response (MR) (18%), 18 stable disease (64%), 1 progressive disease (3.5%). Median time to response is 2.8 months (range 2.4–11.3). Median duration of response is 8.0 months (range 0.6–16.8. Progression free survival at 12 months is 83.1% (95% CI 70.5–98.0%) and median progression free survival has not reached. Nine patients (24%) discontinued treatment: 3 for progressive disease, 4 adverse events (3 alanine aminotransferase increase, 1 paronychia), 2 for other reasons. CONCLUSION: Trametinib is a potentially effective targeted therapy for patients with recurrent/refractory PLGG. Overall treatment is well tolerated. This ongoing trial will continue to gather data on response rate, duration of response and safety of trametinib for PLGG.